Pengaruh Pencampuran Alginat Dan Serbuk Kalsium Oksida (CaO) Adsorben Untuk Peningkatan Kadar Alkohol Teknis Pada Metode Destilasi-Adsorpsi: Pengaruh Pencampuran Alginat Dan Serbuk Kalsium Oksida (CaO) Adsorben Untuk Peningkatan Kadar Alkohol Teknis Pada Metode Destilasi-Adsorpsi - Arifin; Mahirullah, Mahirullah; Lamuru, Afrianti S; Ningsih, Nining Widiana (Jurnal Jejaring Matematika dan Sains, 2023)
This study examines the effect of adding alginate to Calcium Oxide (CaO) powder as an adsorbent pallets in the process of increasing the alcohol levels using the adsorption distillation method. The adsorption distillation method is one of the methods that can be used in alcohol purification. Pure alcohol can be used as an alternative fuel or as an additive in fuel so that it can increase the octane number and produce environmentally friendly exhaust gases. The purpose of this study was to determine the effect of varying alginate concentrations on mixing calcium oxide (CaO) powder to increase technical ethanol content. Alginate concentrations used were 1%, 1.5%, 2%, 2.5% and 3%. The feed ethanol used is 70% and 96% ethanol. The results showed that the optimum concentration of alginate mixed with Calcium Oxide (CaO) powder to become an adsorbent to increase the ethanol content was 2.5%, which increased the ethanol content from 70% to 89% and from 96% to 98.25%. The pore volume of the adsorbent with the addition of 2.5% alginate was 0.89 ml. The ipenelotian results show that the effect of adding alginate to calcium oxide powder can affect the pore density of the alginate gel on calcium oxide powder. The pore density will affect the pore volume of the adsorbent. The increase in pore volume indicates that more adsorbent pores are formed. The more the number of pores in the adsorbent, the ability of the adsorbent to absorb water increases.